2011
DOI: 10.1039/c1sm05610g
|View full text |Cite
|
Sign up to set email alerts
|

Switching of self-assembly in a peptide nanostructure with a specific enzyme

Abstract: Peptide self-assembly has been shown to be a useful tool for the preparation of bioactive nanostructures, and recent work has demonstrated their potential as therapies for regenerative medicine. In principle, one route to make these nanostructures more biomimetic would be to incorporate in their molecular design the capacity for biological sensing. We report here on the use of a reversible enzymatic trigger to control the assembly and disassembly of peptide amphiphile (PA) nanostructures. The PA used in these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
144
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(147 citation statements)
references
References 61 publications
2
144
0
1
Order By: Relevance
“…We now added a fifth design principle 25 : 5) use a catalyst to enhance the rate of the final bond forming reaction leading to formation of the assembling molecule. To various degrees, these principles have been applied to controlling self-assembly through enzymatic catalysis 26,27,28,29,30,31 and synthetic catalysis 32,33 . Figure 1.…”
Section: Concept and Motivationmentioning
confidence: 99%
“…We now added a fifth design principle 25 : 5) use a catalyst to enhance the rate of the final bond forming reaction leading to formation of the assembling molecule. To various degrees, these principles have been applied to controlling self-assembly through enzymatic catalysis 26,27,28,29,30,31 and synthetic catalysis 32,33 . Figure 1.…”
Section: Concept and Motivationmentioning
confidence: 99%
“…The first example of the use of an alkaline phosphatase to trigger the formation of a hydrogel by the dephosphorylation of 9-fluorenylmethoxycarbonyl (Fmoc)-tyrosine phosphate [18][19][20] preceded several others. [21][22] Hirst et al have shown that the amount of biocatalyst used can direct the self-assembly pathway resulting in (kinetic) control of the supramolecular organization of the final supramolecular structure. 23 They also demonstrated that these kinetically locked gels may be ÔunlockedÕ to access a minimum energy state by performing a heat/cool cycle.…”
Section: -2mentioning
confidence: 99%
“…Peptide-based hydrogels have prominent advantages over traditional polymeric hydrogels which include biodegradability, low bioaccumulation and toxicity, spontaneous formation without the use of harmful reagents (such as chemical crosslinkers), and the facile incorporation of cell-specific bioactive moieties. Peptide-based hydrogels are also cost effective, easily synthesized and responsive to external stimuli, including temperature, ionic strength, pH, light, enzyme and magnetic fields [41][42][43][44][45][46][47]. The responsiveness of these peptide hydrogels to biological stimuli attributed to their ability to sense changes to the local environment and release therapeutics in a controlled manner [47].…”
Section: Self-assembling Peptide Designs and Hydrogel Formationmentioning
confidence: 98%
“…Peptide-based hydrogels are also cost effective, easily synthesized and responsive to external stimuli, including temperature, ionic strength, pH, light, enzyme and magnetic fields [41][42][43][44][45][46][47]. The responsiveness of these peptide hydrogels to biological stimuli attributed to their ability to sense changes to the local environment and release therapeutics in a controlled manner [47]. The hydrogelation of peptide hydrogels is easily modified through the attachment of chemical and biological moieties [48].…”
Section: Self-assembling Peptide Designs and Hydrogel Formationmentioning
confidence: 98%